Prediction of the consistency of pituitary adenomas based on multiphoton microscopy. (28th February 2019) - Fang, Na; Wu, Zanyi; Jiang, Changzheng; Wang, Xingfu; Kang, Dezhi; Li, Lianhuang; Chen, Yupeng; Tu, Haohua; Cai, Shanshan; Lin, Yuanxiang; Chen, Jianxin
Abstract: Consistency of pituitary adenomas is an important variable in the surgical resection of these lesions. Preoperative evaluation of tumor consistency will be useful in guiding the operative approach. In this study, multiphoton microscopy (MPM) was used to evaluate the consistency of pituitary adenomas by combining qualitative and quantitative approaches. Three types of pituitary adenomas with different consistencies were first observed through the MPM imaging system to provide the cellular micro-structural details from fresh and unstained tissue samples. The morphologies of cell and collagen were clearly discerned by the endogenous second harmonic generation (SHG) signal from collagen and two-photon excited fluorescence (TPEF) signal from nicotinamide adenine dinucleotide and flavin adenine dinucleotide. Furthermore, R SHG/TPEF (the ratio of the maximum SHG signal over the maximum TPEF signal) and collagen content were calculated as quantitative parameters, which would provide an objective standard for evaluation of the tumor consistency. With the development of multiphoton endoscopy for in vivo imaging, MPM would provide the accurate estimation of the adenoma consistency and help neurosurgeons select appropriate surgical methods during surgery.